177k views
4 votes
Convert y = x^2 + 2x - 5 into the form y-k = a( x- h)^2

User Zsitro
by
6.3k points

1 Answer

3 votes

Answer:


y+6=(x+1)^(2)

Explanation:

we have


y=x^(2)+2x-5

This is the equation of a vertical parabola open upward (because the leading coefficient is positive)

The vertex is a minimum

The equation of a vertical parabola into vertex form is


y-k=a(x-h)^2

where

(h,k) is the vertex of the parabola

Convert the equation into vertex form

Move the constant term to the left side


y+5=x^(2)+2x

Complete the square


y+5+1=x^(2)+2x+1


y+6=x^(2)+2x+1

Rewrite as perfect squares


y+6=(x+1)^(2)

therefore


a=1\\h=-1\\k=-6

The vertex is the point (-1,-6)

User Rajdeep Dosanjh
by
5.8k points